Earlier sea-ice melt extends the oligotrophic summer period in the Barents Sea with low algal biomass and associated low vertical flux. (April 2023) - Kohlbach, Doreen; Goraguer, Lucie; Bodur, Yasemin V.; Müller, Oliver; Amargant-Arumí, Martí; Blix, Katalin; Bratbak, Gunnar; Chierici, Melissa; Dąbrowska, Anna Maria; Dietrich, Ulrike; Edvardsen, Bente; García, Laura M.; et al.
Highlights: Summer protist community in later seasonal stage in year with early sea-ice retreat. Biomass allocation within the microbial food web dependent on sea-ice conditions. A longer open water season will lengthen the oligotrophic low biomass period. Potential consequences for carbon export and trophic transfer. Abstract: The decrease in Arctic sea-ice extent and thickness as a result of global warming will impact the timing, duration, magnitude and composition of phytoplankton production with cascading effects on Arctic marine food-webs and biogeochemical cycles. Here, we elucidate the environmental drivers shaping the composition, abundance, biomass, trophic state and vertical flux of protists (unicellular eukaryotes), including phytoplankton, in the Barents Sea in late August 2018 and 2019. The two years were characterized by contrasting sea-ice conditions. In August 2018, the sea-ice edge had retreated well beyond the shelf break into the Nansen Basin (>82°N), while in 2019, extensive areas of the northwestern Barents Sea shelf (>79°N) were still ice-covered. These contrasting sea-ice conditions resulted in marked interannual differences in the pelagic protist community structure in this area. In August 2018, the protist community was in a post-bloom stage of seasonal succession characterized by oligotrophic surface waters and dominance of small-sized phytoplankton and heterotrophic protists (predominantly flagellates and ciliates) at most stations. In 2019, a higher contribution of autotrophs and large-celled phytoplankton, particularly diatoms, to total protist biomass compared to 2018 was reflected in higher chlorophyll a concentrations and suggested that the protist community was still in a late bloom stage at some stations. It is noteworthy that particularly diatoms contributed a considerably higher proportion to the protist biomass at the ice-covered stations in both years compared to the open-water stations. This pattern was also evident in the higher vertical protist biomass flux in 2019, dominated by dinoflagellates and diatoms, compared to 2018. Our results suggest that the predicted transition toward an ice-free Barents Sea will lengthen the oligotrophic summer period with low algal biomass and associated low vertical flux.